Therapeutic effect of vitamin D in acute lower respiratory infection: A randomized controlled trial. (August 2017) - Somnath, Sanjana H.; Biswal, Niranjan; Chandrasekaran, Venkatesh; Jagadisan, Barath; Bobby, Zachhariah
Summary: Objectives: To study the effect of vitamin D supplementation on the outcome of acute lower respiratory infection in hospitalized children. Study design: This is an open label parallel group randomized trial. Total of 154 children aged 2 mo–5 yrs (mean age 13 mo) admitted with acute lower respiratory infection (ALRI) were randomized to receive standard care therapy alone or standard care therapy for the respiratory infection along with a single oral dose of 100, 000 IU of vitamin D3. Serum 25(OH)D levels were measured at admission in all the children and 72 h after administration of vitamin D in the supplemented group. Primary outcome measured was the duration of hospital stay. Secondary outcomes measured were mortality, incidence of complications, admission to PICU and recurrence of respiratory infections within 90 days of discharge. Primary outcome was compared using Mann Whitney U test and secondary outcomes were compared using chi-square or Fischer's exact test. Results: Baseline characteristics were comparable between the two groups. There was no statistically significant difference in the primary outcome (Median duration of hospital stay in both the groups) and also in secondary outcomes (mortality, PICU admission, complications and recurrence of respiratory infections within 90 days of discharge). Conclusion: Single oral dose of 100, 000 IU of vitamin D3 did not lead to reduction in duration of hospital stay, mortality, PICU admission or complications related to ALRI when compared to standard therapy alone in under five children hospitalized with ALRI but was able to achieve serum vitamin D sufficiency within 72 h of administration. Registered under clinical trial Registry of India Identifier no: CTRI/2014/09/005032.